Memahami Konsep Dasar Manajemen Peserta Didik - Mohamad Muspawi (Universitas Batanghari Jambi, 2020)
Student management is a process for managing all forms of activities related to students and other resources in order to achieve educational goals effectively and efficiently. There are several management principles for students: 1) All activities must refer to applicable regulations. 2) Can be viewed as part of the overall management of the institution. 3) More intended to unite students who have a variety of backgrounds and differences to then be directed to understand and respect each other. 4) In its activities, student management is directed as an effort to regulate the potential development of students. 5) In the management of student activities must be able to encourage and spur the potential independence of students. 6) The life activities of students, both at school and in the future, student management must run functionally.